An extended best-worst multi-criteria decision-making method by belief functions and its applications in hospital service evaluation. (April 2020) - Fei, Liguo; Lu, Jiandong; Feng, Yuqiang
Highlights: The traditional BWM is extended to uncertain environments by the theory of belief function. Evidential BWM can determine weight of criteria and alternatives with regard to different criteria. A novel MCDM framework is constructed based on the evidential BWM. Evidential BWM is employed to a hospital service evaluation problem innovatively. Abstract: In the healthcare industry, hospital service quality assessment is an important work, which can not only promote medical service providers to improve the status quo of the industry, but also ensure patients to enjoy better service. Since hospital service evaluation involves a great many qualitative and quantitative factors, it is a complex multi-criteria decision-making (MCDM) issue. In the real-life MCDM problems, the ambiguity of information expression often occurs because of the lack of complete knowledge, and the vagueness of decision makers in qualitative judgment is quite common, so the crisp values of criteria may be inadequate to deal with such complex situations. To achieve the evaluation of hospital service quality under uncertain environment, in this paper, the traditional best-worst method (BWM) is extended based on belief function theory (BFT) that has powerful ability of uncertain expression and reasoning. This paper describes in detail the implementation process of evidential BWM and the proposed hospital service quality evaluation framework based on it. A case study is presented to evaluate hospital service quality based on the constructed model. The results manifest the effectiveness of the proposed method and offer an insightful reference for the evaluation of healthcare industry.